The Effect of Working Capital Turnover and Receivable Turnover on Profitability: Case Study on PT. Merck Tbk - Wiwiek Mardawiyah Daryanto; Fajar Rachmanto (International Journal of Business Studies, 2018)
With the growing world ofbusiness, the competition between similar companies getting tighter. To maintain the viability of a company required a good management of resources conducted by the management. Account Receivable turnover and working capital are very important for a company because it is the elements in measuring the proitability of the company. The purpose of this research is to know: (1) the effect of account receivable turnover to company proitability, (2) the effect ofworking capital turnover to the company, (3) the effect of account receivable turnover and working capital turnover to company proitability. The research method used is quantitative analysis, correlation coeficient test, the coeficient of determination test and hypothesis test. The data used in this study is secondary data sourced from inancial statement PT. Merck Tbk period 2009-2013 obtained directly from the respondent. The results based on multiple linear regression tests showed that simultaneously turnover of account receivable and working capital turnover did notsigniicantly affect company proitability (5.603 < 9.55). Partially, the account receivable turnover does not signiicantly affect the proitability of the company (2.298 < 3.182) and the working capital turnover does not signiicantly affect the proitability of the company (3.003 < 3.182). So, it can be said the hypothesis in this study was rejected.